Existence of Criminal Sanctions for Alleged Violations of the Right to Association - Feliks, Danggur; Wijayanti, Asri; Prasetyo, Rudy Wahyu (Riwayat: Educational Journal of History and Humanities, 2025)
The urgency of this research is the realization of a sense of justice from the perspective of labor law on the violation of the right to association based onthe Sustainable Development Goals(SDGs)Point8.8.2. The existence of changes in legal rules on the possibility of alternative settlement of labor crimes with the threat of criminal sanctions of less than five years through restorative justice, has resulted in social conflicts and disruption of the conduciveness of industrial relations and national stability. A labor law review of the violation of the right to association based onSDGs point8.8.2The purpose ofthis study is to find out the existence of criminal sanctions for the violation of the right to union.This research method uses a normative juridical approach withastatute approachanda case approach.The result of the studyis the existence of criminal sanctions for violations of the right to association, based on the existence of strong evidence. Meanwhile, in practice, there is a clash with the existing evidence showing that the case is not a case in the field of criminal law but a case in the field of industrial relations dispute law that falls into the territory of civil law.